2021
DOI: 10.3389/fcvm.2021.650147
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Outcome of Postoperative Atrial Fibrillation After Cardiac Surgery—A Propensity Score-Matched Cohort Analysis

Abstract: Background: Postoperative atrial fibrillation (POAF) results in a longer hospital stay and excess mortality. However, whether POAF would increase stroke rate has been debated for years. When and how long should anticoagulation be used to prevent stroke are unknown. In the study, we planned to investigate the clinical demographics and long-term outcomes of POAF after cardiac surgery in a single-center cohort.Methods: The cohort study used a database from National Taiwan University Hospital, a single tertiary me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
2
8
0
1
Order By: Relevance
“…But we saw a statistically significant difference with a threefold increase in death among patients that developed POAF post-CABG. Our finding concurs with a recent paper by Emma Thorén et al [83] where POAF was associated with mortality with a more recent paper from Taiwan which also concluded that in the Asian population, POAF is significantly correlated with an overall mortality [84].…”
Section: Post-operative Outcomessupporting
confidence: 93%
“…But we saw a statistically significant difference with a threefold increase in death among patients that developed POAF post-CABG. Our finding concurs with a recent paper by Emma Thorén et al [83] where POAF was associated with mortality with a more recent paper from Taiwan which also concluded that in the Asian population, POAF is significantly correlated with an overall mortality [84].…”
Section: Post-operative Outcomessupporting
confidence: 93%
“…Among the 8974 identified (6212 screened) articles, a total of 59 studies published between 1993 and 2022 were included in the present analysis. 3 , 4 , 5 , 7 , 12 , 13 , 14 , 15 , 16 , 17 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Many episodes of POAF are self-terminating and some are asymptomatic, but POAF has been associated with a four- to the five-fold risk of recurrent AF in the next 5 years. It has also been shown to be a risk factor for stroke, myocardial infarction, and death compared with non-postoperative AF patients [ 3 , 4 ]. The pathogenesis of POAF may be multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of POAF are complex and incompletely defined, but include intraoperative and postoperative phenomena, such as inflammation, sympathetic activation, hypoxia, acidosis, oxidative stress, electrolyte abnormalities, and intra-atrial conduction delay that combine to trigger atrial fibrillation, often in the presence of pre-existing factors, making the atria vulnerable to atrial fibrillation induction and maintenance [ 1 , 2 ]. To prevent POAF, preoperative beta-blocker (propranolol, carvedilol plus N-acetyl cysteine) use is associated with a reduced incidence of postoperative AF, but not major adverse events such as death, stroke, or acute kidney injury [ 3 ]. Data for other interventions such as statins, magnesium, colchicine, posterior pericardiotomy, atrial pacing, and corticosteroids are not robust.…”
Section: Introductionmentioning
confidence: 99%